THE ROLE OF BIG DATA IN DECISION MAKING FOR ENTREPRENEURS HIP THROUGH THE USE OF INFORMATION SYSTEMS IN E-COMERCE - Tantri Aprilia; Dr. Achmad Fauzi, S.E., MM; Ahmad Muchlisin Natas Pasaribu; Arif Musyaffa; Herlin Rahmasari; Iqbal Al Baihaqi; Nabila Alifiyah Gunawan; Muhammad Yusuf Nugroho (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
The use of information systems contained in E-commerce which of course will be very important to help someone who is about to enter the world of entrepreneurship, the role of the information system is also inseparable from the development of the digital world which is also inseparable from the role of big data itself. This journal will discuss the role of big data which stores a lot of data needed, then this data will be processed in the information system that exists in the E-commerce system so that it will produce very important information to help someone in making decisions for entrepreneurship and will also discuss components in each discussion. The purpose of this research is expected to be additional information to help someone in making decisions in entrepreneurship and also become an additional reference if there is further research. The methods to be used are qualitative methods and literature studies obtained from previous scientific journals and articles.